Implementasi Metode SAW dan MABAC Pada Sistem Pendukung Keputusan Penerima Beasiswa Anak Tempatan - Sari Misriana; Fajar Ratnawati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Bengkalis Regency Education Office (Disdik) provides Local Children's Scholarships to students in an effort to help students to alleviate the dependents of the Single Tuition Fee (UKT) in pursuing education. In determining the recipient of the Tempatan Children's Scholarship, the Education Office government carries out several stages manually such as collecting all the files of students who register, after which the Education Office checks the completeness of the student files one by one, gives a value for each predetermined criterion and manually calculates the value of the criteria. A decision support system for recipients of web-based Local Children's Scholarships is needed to help determine recipients of Local Children's Scholarships to be faster and more accurate. This system is made using the Simple Additive Weighting (SAW) method and Multi Attributive Border Approximation Area Comparison (MABAC) to facilitate the calculation and comparison of the value of each alternative in the system, by determining the ranking based on the largest value as the best alternative. The result of the application of the SAW and MABAC methods in the system is that the system displays alternative data sequentially based on rankings that can help in determining the recipient of the Local Children Scholarship. From 60 field data, the application of SAW and MABAC methods on this system has an accuracy of 83.3%. The development method used is the Extreme Programming method.